Instalación y configuración de central telefónica IP-PBX para intercomunicación del AEIRNNR. - Quiñones Reinoso, Edison Stalin (2014)
The Telephony IP is a technology that allows to integrate in oneself net based on protocol IP the voice communications and data. When we speak of a telephony system IP we are speaking of a group of elements that properly integrated they allow to give a telephony service (based on VoIP). The basic elements that form this system are: the switchboard IP (IP-PBX), the Gateway IP and the different telephones IP. Elastix is an application software to create systems of Telephony IP that integrates the best available tools for PBX based on Asterisk in a simple and easy interface of using. He also adds their own group of utilities and it allows the creation of modules of third to make of this the best package of available software for the telephony of open code. Elastix is a distribution free of Servant of Unified Communications that it integrates in a single package: VoIP PBX, Fax, Instantaneous Messaging, Electronic mail, Collaboration. The goal of Elastix is the dependability, modularity and easy use. These characteristics added to the robustness to report make of the, the best option to implement a PBX based on Asterisk. Elastix implements great part of its functionality on four very important software programs as they are Asterisk, Hylafax, Openfire and Postfix. These offer the functions of PBX, Fax, Instantaneous Messaging and Electronic mail respectively.